Prevalence of carbapenem resistant bacterial strains isolated from different clinical samples: study from a tertiary care hospital in Kathmandu, Nepal - Karn, Sitesh; Pant, Narayan Dutt; Neupane, Sanjeev; Khatiwada, Saroj; Basnyat, Shaila; Shrestha, Basudha (Journal of Biomedical Sciences, 2017)
Background Carbapenems are considered as drugs of choice for the treatment of the infections caused by drug resistant bacteria. However, in the recent years the prevalence of carbapenem resistant gram negative bacteria has increased significantly. The main objective of this study was to determine the prevalence of carbapenemase producing gram negative bacteria among all the clinical isolates. Material and methods A total of 3246 non-repeated, different clinical specimens from patients attending Kathmandu Model Hospital, from July 2013 to January 2014 were cultured and the gram negative bacterial isolates obtained were subjected to identification with the help of colony morphology, Gram’s stain and conventional biochemical tests. Kirby-Bauer disk diffusion technique was used to perform antimicrobial susceptibility testing. Phenotypic confirmation of carbapenemase and AmpC beta-lactamase production was done by combined disc method. Results 890 samples showed the growth of bacterial pathogens. Out of total 769 gram negative bacteria, 57 were found to be carbapenem resistant. Of which, highest number (47) of the isolates were found to be metallo-β lactamase (MBL) producers. Six bacterial isolates produced both (Klebsiella pneumoniae carbapenemase) KPC and MBL, whereas only one isolate was found to be positive for both MBL and AmpC. Three bacterial strains showed carbapenem resistance due to over production of AmpC β-lactamase. Conclusion Among carbapenem resistant gram negative bacteria, MBL was present as the major enzyme responsible for resisting carbapenem antibiotics.